Analisis DAMPAK DINAMIKA PANDEMI COVID-19 TERHADAP RETURN INDEKS SAHAM SEKTOR FINANCE DI BURSA EFEK INDONESIA - Lumbantoruan, Frizt Yonif Yongly; Tubagus Ismail; Ira Geraldina (FEB Universitas Sam Ratulangi Manado, 2023)
The significant changes in the return of the Financial Sector Stock Index both before and after the COVID-19 pandemic entered Indonesia have been the focus of attention in this study. In the midst of this uncertain condition, the Financial Sector Stock Index on the Indonesian Stock Exchange experienced noticeable changes. This research focuses on analyzing the impact of the COVID-19 pandemic on the return of the Financial Sector Stock Index on the Indonesian Stock Exchange. The study involves the Financial Sector Stock Index as the research object, with research variables including Gross Domestic Product (GDP), Inflation Rate, and Return of the Financial Sector Stock Index. The research also examines the consistency of the relationship between GDP, inflation, and stock returns over a considerable period. The study period covers from 2019 to 2022. This research is of a quantitative nature. The model used to address the research question is the Structural Vector Autoregression (SVAR) model. The research tool in this SVAR model uses the Eviews software. Secondary data is used in this study. The research population consists of 20 companies in the finance sector listed on the Indonesian Stock Exchange during the study period. The results of the Granger causality test show that inflation has a significant relationship with the return of the financial sector stock with a probability value of 0.0382. However, variance decomposition illustrates that the contribution of inflation to changes in stock returns is not very large, at 3 percent from period one to period sixteen. Meanwhile, GDP to the return of the financial sector stock index has a probability value of 0.0916 from the Granger causality test results. This means that GDP does not have a significant relationship with the return of the financial sector stock during the observation period.